2016
DOI: 10.1016/j.cej.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Rejection of ammonium and nitrate from sodium chloride solutions by nanofiltration: Effect of dominant-salt concentration on the trace-ion rejection

Abstract: In this work, the rejection of two ions associated with fertilizer pollution of ground water (NH4and NO3) by a polyamide nanofiltration (NF270) membrane was studied. Sodium chloride was selected as the dominant salt and the effect of its concentration on the NH4 and NO3 rejections was evaluated. Filtration experiments were carried out in a cross-flow setup with a rectangular spacer-filled feed channel. The solution-diffusion-electro-migration-film model (SDEFM), previously developed to model the pressure-drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…resulting in negative rejection values, which in turn made the rejection of positively charged metal species higher. It is reported that membrane permeances to both salt and ions are dependent on total electrolyte concentration 24 [43]. In this study, values of permeance to single charge ions showed variations mostly lower than 10% over the 25 ionic strength (IS) range evaluated (from 1.5x10 -1 M at pH = 1 to 5x10 -2 M at pH = 2.5), while permeance values to 26 ions with higher charge decreased with the increase of IS.…”
mentioning
confidence: 63%
“…resulting in negative rejection values, which in turn made the rejection of positively charged metal species higher. It is reported that membrane permeances to both salt and ions are dependent on total electrolyte concentration 24 [43]. In this study, values of permeance to single charge ions showed variations mostly lower than 10% over the 25 ionic strength (IS) range evaluated (from 1.5x10 -1 M at pH = 1 to 5x10 -2 M at pH = 2.5), while permeance values to 26 ions with higher charge decreased with the increase of IS.…”
mentioning
confidence: 63%
“…Figure shows the furfural rejection percentage using NF and RO membranes as a function of the trans‐membrane flux ( J v ), applying TMP from osmotic pressure to 20 bar. According to the solution‐diffusion model, it is noted that rejections increase with trans‐membrane flux until a constant plateau is reached …”
Section: Resultsmentioning
confidence: 99%
“…According to the solution-diffusion model, it is noted that rejections increase with trans-membrane flux until a constant plateau is reached. 39,42 In regard to furfural rejection, NF membranes showed different behavior between them, whereas the performance of RO membranes was similar. As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations